2021
DOI: 10.1108/aaouj-02-2021-0025
|View full text |Cite
|
Sign up to set email alerts
|

The transformation of education during the corona pandemic: exploring the perspective of the private university students in Bangladesh

Abstract: PurposeIn 2020, the education system was preliminary halted by the COVID-19 crisis and went through radical improvisation, and online-based distance learning was the only plausible initiative to continue educational activities ensuring health guidelines properly. However, in reality, such desperate measure in case of a lower-middle-income developing nation lacking proper structural capabilities raised some issues and concerns for both pupils and mentors, and this study aims to explore the practice of online-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 17 publications
1
42
0
Order By: Relevance
“…The study further revealed that slow internet, interrupted power supply, attention problems, and difficulty with understanding lessons are the major barriers to effective learning on online platforms. Similar findings were found in another study where the author showed inadequate technical infrastructure, limited device or internet accessibility, financial constraints, lack of technical literacy, and psychological inertia among both teachers and students disrupted the harmony of the online learning experiences [14]. Another study claimed students are not ready for e-learning yet, and the majority of them (86%) feel that e-learning has little impact on their learning outcomes and prefer the F2F teaching-learning strategy [15].…”
Section: Introductionsupporting
confidence: 82%
“…The study further revealed that slow internet, interrupted power supply, attention problems, and difficulty with understanding lessons are the major barriers to effective learning on online platforms. Similar findings were found in another study where the author showed inadequate technical infrastructure, limited device or internet accessibility, financial constraints, lack of technical literacy, and psychological inertia among both teachers and students disrupted the harmony of the online learning experiences [14]. Another study claimed students are not ready for e-learning yet, and the majority of them (86%) feel that e-learning has little impact on their learning outcomes and prefer the F2F teaching-learning strategy [15].…”
Section: Introductionsupporting
confidence: 82%
“…In other words, OCP, COA, affects both ICTR and EOC, whereas, CF only affects EOC. Studies revealed that ICT readiness is an important requirement for students and teachers for an effective OCP (El Mansour and Mupinga, 2007; Dias and Diniz, 2014; OECD, 2020; Shahriar et al. , 2021; Al-Amin et al.…”
Section: Resultsmentioning
confidence: 99%
“…It is well established that ICT readiness or ICT infrastructure is a crucial requirement for effective online education (Dias and Diniz, 2014; OECD, 2020; Hamid et al. , 2021; Shahriar et al. , 2021; Al-Amin et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This rapid technological progress is marked by almost all community activities using technology systems, including in the world of education. That learning and teaching around the world has gone through a transformation (Getuno et al, 2015;Leal Filho et al, 2018;Shahriar et al, 2021). This transformation can be seen through the presentation of current learning, that the presentation of conventional learning is now supported by teaching materials or materials that utilize technology, information and communication (Santosa et al, 2017).…”
Section: Introductionmentioning
confidence: 99%